Eid songs - Gillani, Fawzia (GOODWORD BOOKS New Delhi, 2022)
"Eid Songs" celebrates the joy and unity of the Eid festival through a collection of heartfelt poems and melodies. It captures the essence of family, tradition, and the spirit of giving, inviting readers to embrace the festive spirit and shared moments of happiness.